Potential Protective Role of 14-3-3 Protein in Pathological Cardiac Hypertrophy Through The Regulation of Endoplasmic Reticulum Stress: Role of Calreticulin - Flori R. Sari; Rajarajan A Thandavarayan; Vivian Soetikno (The Avicenna Medical Journal, 2021)
Introduction: 14-3-3 protein plays an important role in protecting cardiac cells from hypertrophy and endoplasmic reticulum stress during pressure overload elicited by aortic banding (AB) surgery; however, the relation among these protective roles is largely unknown. Methods: We investigated the in vivo role of 14-3-3 protein in two protocols involving C57/BL-6 mice and dominant negative (DN) 14-3-3η mice subjected to three- or seven-days pressure overload stimulation by applying AB surgery. The protein expressions of cardiac hypertrophy and ER stress markers, including atrial natriuretic peptide (ANP), galectin-3, glucose-regulated protein (GRP)78, calreticulin as well as 14-3-3 protein was analyzed by western blot. Results: Three- or seven-day pressure overload stimulation significantly increased the heart weight/body weight (HW/BW) ratio; cardiomyocyte diameter; and the protein expression levels of ANP, GRP78 as well as 14-3-3 in the C57/BL-6 mice. Partial inactivation of 14-3-3 protein in the DN 14-3-3η mice significantly increased the protein expression of ANP, Galectin-3, GRP78, and calreticulin after three- or seven-days AB surgery. Conclusion: These results suggest that 14-3-3 protein, as a molecular chaperone, protects against pathological cardiac hypertrophy, at least in part, by maintaining the normal ER function through the regulation of GRP78 and calreticulin.